Beyond the National Divide : Regional Dimensions of Industrial Relations - Boivin, Jean (Relations industrielles / Industrial Relations, 2006)
The article reviews the book, "Beyond the National Divide : Regional Dimensions of Industrial Relations," edited by Mark Thompson, Joseph B. Rose and Anthony E. Smith.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z